1990
DOI: 10.1007/bf02550407
|View full text |Cite
|
Sign up to set email alerts
|

Volume change of the prostate and seminal vesicles in male hypogonadism after androgen replacement therapy

Abstract: Before and after androgen replacement therapy prostatic and seminovesicular volume was estimated by means of transrectal ultrasonography in 13 hypogonadal men. Volume of the prostate (p less than 0.001) and seminal vesicles (p less than 0.01) significantly increased after treatment with testosterone enanthate. However, the plasma level of testosterone remained abnormally low. These results indicate that volume determination of the prostate and seminal vesicles by means of transrectal ultrasonography is suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 10 publications
1
32
1
Order By: Relevance
“…This has also been reported in hypogonadal males with primary hypogonadism where a significant increase in PV has been observed with TRT. In a study of 13 men with Klinefelter's syndrome between the ages of 25 and 32 years, TRT was shown to result in an increased PV (from 9.3 to 19.0 mL) when compared to the control (18.7 mL, no change in volume) ( P ≤ 0.001) …”
Section: Discussionmentioning
confidence: 98%
“…This has also been reported in hypogonadal males with primary hypogonadism where a significant increase in PV has been observed with TRT. In a study of 13 men with Klinefelter's syndrome between the ages of 25 and 32 years, TRT was shown to result in an increased PV (from 9.3 to 19.0 mL) when compared to the control (18.7 mL, no change in volume) ( P ≤ 0.001) …”
Section: Discussionmentioning
confidence: 98%
“…This study suggests that administration of exogenous testosterone to middle‐aged and older men with sexual and/or urinary dysfunction symptoms may retard or reverse age‐related prostate growth. Previous studies of the effects of exogenous testosterone on prostate size and PSA concentrations are mostly limited to hypogonadal men (Canale et al ., 1990; Sasagawa et al ., 1990; Behre et al ., 1994; Meikle et al ., 1997; Ozata et al ., 1997; Snyder et al ., 2000; Jin et al ., 2001). Generally these have shown that testosterone administration increases prostate volume from subnormal to age‐appropriate (Behre et al ., 1994) or smaller (Jin et al ., 2001) prostate volumes.…”
Section: Discussionmentioning
confidence: 99%
“…An atrophic prostate and seminal vesicles are typically observed in male hypogonadism. Androgen replacement therapy in male hypogonadism occasionally restores male secondary sexual characteristics and male sexual behavior [17,18], Furthermore, androgen replacement restores the ejaculate volume, mostly derived from the prostate and seminal vesicles, to normal [19], Sasagawa et al [20] reported that in evaluating the adequacy of androgen replacement therapy in male hypogonadism, volume esti mation of these accessory glands by ultrasonography ap pears to be more suitable than plasma testosterone deter mination. Since the volume of seminal vesicles may decrease after ejaculation, as shown in the present study, it seems important to maintain a period of abstinence when evaluating the adequacy of androgen replacement by the seminal vesicle volume.…”
mentioning
confidence: 99%